METHODOLOGICAL ROLE IN FORMING DIGITAL REFLECTION IN ELECTRONIC EDUCATION - Salikhova Muhayyo Shakirovna; Avulova Fatima Almardon qizi (Western European Studies, 2026)
This article analyzes the process of forming digital reflection in students in an electronic learning environment and the role of methodological approaches in this process. In education organized on the basis of digital technologies, reflection is considered as one of the important factors in improving the quality and effectiveness of education. The article covers methods, tools and pedagogical opportunities that serve to develop digital reflection
Keywords: Electronic education; digital reflection; methodological approach